Capital Budgeting Practices of Listed Philippine Firms - Echanis, Erlinda S.; Kester, George W. (Philippine Management Review; Vol 7 (1997), 2016)
The paper examines the disparity between theory and practice in the use of quantitative techniques in the evaluation of capital expenditures by publicly-listed Philippine firms.  Survey questionnaires were mailed to all 185 publicly-listed Philippine firms in 1996 of which forty-one firms responded representing 22.2% of the total.  The questionnaire focused on:  1) the constraints on the size of the firm’s capital budget; 2) the quantitative evaluation techniques used in the evaluation of capital investments; and 3) determination of discount rates for evaluating proposed capital investments.  Results of the survey showed that publicly-listed Philippine firms apply the same quantitative techniques applied by firms in such developed countries as the U.S. and U.K. in the evaluation of capital expenditures.  Between the NPV and the IRR, more Philippine firms use the IRR.  The popularity of the payback period method was also confirmed by the survey results in this study.  The payback period method ranked second to IRR while NPV ranked third only.  Lastly, respondent firms selected discount rates that were easier to determine or simpler than the WACC.  These are:  the cost of specific capital used for the project and the t-bill rate plus premium.